The Packaging of Politics in the Journal of the Canadian Historical Association: Embedded, Embodied, Splintered, and Repeated - Bryden, P. (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association / La Société historique du Canada, 2023)
This article examines the political history, broadly defined, that has been published in this journal since its inception, arguing that there has been both change and continuity. While politics is no longer as essential to the history that is published, as was the case in the 1920s and 1930s, nor as driven by biography, as became common following the Second World War, the political history subfield remains vibrant and there are still themes and topics that continue to intrigue and to which scholars return repeatedly.